Revenue Mobilization and Contribution Patterns in Nepal - Nepal, Pramshu; Upadhyaya, Yadav Mani; Dhakal, Hem Chandra (Interdisciplinary Journal of Management and Social Sciences, 2024)
The objective of this article is to evaluate the revenue mobilization efforts in Nepal and understand the contribution patterns of various revenue sources. In this article data of gross domestic product (GDP) and total revenue for the fiscal years 2017/18 to 2021/22was collected from publication of IRD of Nepal. It examines key aspects of fiscal federalism, including revenue collection rights, revenue sharing, and intergovernmental fiscal transfers, as governed by the Intergovernmental Fiscal Arrangement Act. The study assesses government revenue as a percentage of GDP, tax revenue efficiency, and the role of the Internal Revenue Department (IRD). It also explores the composition of revenue, distinguishing between tax and non-tax sources. The findings reveal a positive trend in revenue mobilization, with tax revenue playing a significant role. The findings contribute to understanding Nepal’s revenue mobilization efforts and the composition of its revenue sources, providing insights into the country’s fiscal policies and financial sustainability.